Robodogs - Walliams, David; Stower, Adam (UK, 2023)
Dogs make the perfect partners for police. Some breeds can wrestle robbers to the ground. Some can follow the scent of criminals on the run. Some can bark at baddies. But what if one dog could do all of these things and more? It would be the greatest police dog of all time...
Keywords: Adventure; Animal / Dogs; Juvenile Fiction; Police Dogs